PENINGKATAN DAYA GUNA DAN PRODUKTIVITAS PKK BHINEKA NUSA KAUH DALAM KEHIDUPAN SOSIAL BERMASYARAKAT - Putu Ayu Paramita Dharmayanti; Farida Hanum; Ni Nyoman Suryani (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
Bhineka Nusa Kauh Empowerment and Family Welfare Group (PKK) felt its existence and its benefits by the community members in the Banjar Bhineka Nusa Kauh environment in improving family welfare and overcoming problems that arose in the Banjar Bhineka Nusa Kauh environment. In addition to problems related to empowerment and family welfare, there are also problems in the social environment of the community in the Banjar Bhineka Nusa Kauh environment. As for these problems such as issues of cleanliness and environmental sustainability, a sense of solidarity and caring for others, productive skills that can help the economy of families and other citizens. Therefore it is deemed necessary to provide assistance to PKK Bhinneka Nusa Kauh in increasing the usability and productivity of PKK Bhineka Nusa Kauh members, especially problems in social life in order to create tolerance and togetherness. The priority solution to solve the problem through the implementation of the Community Partnership Program (PKM) is to carry out activities in ornamental plants and living kitchens, public speaking training, nutrition counseling and healthy food, entrepreneurship training, and mentoring to nursing homes. PKM is carried out by involving all members of the PKK group, STT, residents and all Banjar Bhineka Apparatuses in Nusa Kauh. Until all activities take place properly and the community is actively involved with enthusiasm because they really feel the good benefits of these activities.